Solubility of U(VI) in chloride solutions. III. The stable oxides/hydroxides in MgCl2 systems: Pitzer activity model for the system UO22+–Na+–K+–Mg2+–H+–OH−–Cl−–H2O(l). (April 2019) - Yalçıntaş, Ezgi; Çevirim-Papaioannou, Neşe; Gaona, Xavier; Fellhauer, David; Neck, Volker; Altmaier, Marcus
Highlights: New Pitzer activity model for the system UO2 2+ –Na + –K + –Mg 2+ –H + –OH − –Cl − –H2 O(l). Uranium(VI) solubility studies in dilute to concentrated MgCl2 solutions. Systematic evaluation of experimental datasets in the NaCl, KCl and MgCl2 systems. Improved geochemical calculations for the nuclear waste disposal safety case. Abstract: We have developed new chemical, thermodynamic and activity models for the system UO2 2+ –Na + –K + –Mg 2+ –H + –OH − –Cl − –H2 O(l) within the Pitzer approach. The new thermodynamic model is based on previously reported data treated within the SIT approach for NaCl and KCl systems, as well as on new experimental data determined in this work for the MgCl2 system. The solubility of uranium(VI) was studied in 0.01–5.15 mol·kgw −1 MgCl2 solutions at pHm  = 4.1–9.7 (with pHm  = −log [H + ]). Experiments were performed under Ar atmosphere at T  = (22 ± 2) °C. In all investigated systems, the solubility of U(VI) is controlled by metaschoepite, UO3 ·2H2 O(cr). In contrast to previously investigated NaCl and KCl systems, no ternary Mg–U(VI)–OH(s) solid phases formed in alkaline MgCl2 solutions within the timeframe of this study (≤ 200 days). A very significant increase in the solubility (up to 3 log10 -units) is observed in acidic to near-neutral pHm conditions when increasing MgCl2 concentration from 0.01 to 5.15 mol·kgw −1, which reflects the strong ion interaction processes taking place in concentrated MgCl2 brines. The solubility of UO3 ·2H2 O(cr) in the investigated NaCl, KCl and MgCl2 solutions is well described with the solubility and hydrolysis constants recommended by Altmaier et al., (2017) and NEA–TDB, and a Pitzer activity model derived in the present work. The latter model considers experimental data reported in the present study and available in the literature for NaCl, KCl and MgCl2 systems (solubility, potentiometric and spectroscopic data), in combination with well-stablished estimation methods and correlations with SIT coefficients. Chemical, thermodynamic and Pitzer activity models provided in this work for the system UO2 2+ –Na + –K + –Mg 2+ –H + –OH − –Cl − –H2 O(l) accurately describe all evaluated datasets, and represent an adequate tool for the calculation of U(VI) solubility and aqueous speciation in a variety of geochemical conditions including concentrated brine systems of relevance in salt-based repositories for nuclear waste disposal.